3x+7=4(2x-2)

Simple and best practice solution for 3x+7=4(2x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+7=4(2x-2) equation:


Simplifying
3x + 7 = 4(2x + -2)

Reorder the terms:
7 + 3x = 4(2x + -2)

Reorder the terms:
7 + 3x = 4(-2 + 2x)
7 + 3x = (-2 * 4 + 2x * 4)
7 + 3x = (-8 + 8x)

Solving
7 + 3x = -8 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
7 + 3x + -8x = -8 + 8x + -8x

Combine like terms: 3x + -8x = -5x
7 + -5x = -8 + 8x + -8x

Combine like terms: 8x + -8x = 0
7 + -5x = -8 + 0
7 + -5x = -8

Add '-7' to each side of the equation.
7 + -7 + -5x = -8 + -7

Combine like terms: 7 + -7 = 0
0 + -5x = -8 + -7
-5x = -8 + -7

Combine like terms: -8 + -7 = -15
-5x = -15

Divide each side by '-5'.
x = 3

Simplifying
x = 3

See similar equations:

| 2a-3(a-5)=5 | | k-(-71)=74 | | c-78=(-10) | | 9x^2=-77+18x | | x^3-10x=-3x^2-24 | | j+4=(-85) | | -87=g-92 | | 2a-3b(a-5)=5 | | w+27=(-64) | | 2/x-22=5/x-2 | | x/7-1=2 | | m-68=-48 | | -5=j+5 | | q-(-9)=73 | | 14c-7d= | | 98=-7z | | 2v-15=25 | | -15=w-62 | | 3x+14=-7+2x | | -4n=(-64) | | 10x^2+81x+8=0 | | h+(-91)=6 | | -8j=88 | | c^2-3c-85=0 | | 10x-11-8x+23=6 | | -9h=-99 | | b-(-12)=15 | | -4u-2(-u-15)=8(2u-9) | | 3=j+-9 | | 17=c-(-7) | | 6n^2+29n+28=0 | | 3Cosx=3 |

Equations solver categories